Pregnancy in the paint and the pitch: Does giving birth impact performance? - Jill S. Harris; David J. Berri (Journal of Economics and Statistics, 2024)
We examine the impact of giving birth on athletic performance of players in the Women's National Basketball Association. Using data from media reports and National Womens Basketball Players Association records we specify a productivity model and use a differences-in-means approach to investigate. We do not find any impact of giving birth on player performance in the sample. In the wake of the Gunnarsdottir maternity leave decision against Club Lyon, this research could help inform league policies concerning maternity leave and also contribute to the broader conversation about gender discrimination in the workplace based on perceptions of productivity before and after giving birth.
Keywords: I13; J23; J24; Z1; 330; elite athlete performance; motherhood penalty; pregnancy; worker productivity